2006
DOI: 10.1007/s11064-005-9002-x
|View full text |Cite
|
Sign up to set email alerts
|

The Birth of Neurochemical Maps

Abstract: The fusion of synaptic vesicles with the plasma membrane during exocytosis can be recorded by membrane capacitance measurements under voltage-clamp conditions. These measurements enable high time-resolution quantitation of exocytosis. The present study was carried out using the above technique to elucidate the effects of various polyunsaturated fatty acids on exocytosis in a neuroendocrine cell, the rat pheochromocytoma-12 (PC12) cell. External application of eicosapentaenoic acid and arachidonic acid resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Our results indicated that EPA itself acts as an enhancer for neuronal differentiation, and EPA did not serve solely as a precursor for DHA. Previous reports have shown different effects of DHA and EPA on neuronal function [29]. In contrast to DHA, it is not clear whether EPA enhanced neuronal differentiation in NSCs in vivo.…”
Section: Discussionmentioning
confidence: 97%
“…Our results indicated that EPA itself acts as an enhancer for neuronal differentiation, and EPA did not serve solely as a precursor for DHA. Previous reports have shown different effects of DHA and EPA on neuronal function [29]. In contrast to DHA, it is not clear whether EPA enhanced neuronal differentiation in NSCs in vivo.…”
Section: Discussionmentioning
confidence: 97%
“…2A), including areas they sampled outside of the hypothalamus that served as a control. Their careful documentation of the sampled area and use of a custom-made micropunch tool (which they also illustrated in their study) anticipates the later use of similar instruments as developed by Palkovits and colleagues to sample discrete parts of the brain [194; 320323] (also see [195]).…”
Section: Molecular Mining Of the Hypothalamusmentioning
confidence: 91%